Augmented reality for tourist routes - Cabeleira, Miguel Tomaz (2024)
In the constantly evolving landscape of global tourism, improving the tourist experience through innovative technologies has become fundamental. The tourism sector, a significant contributor to the global economy, continually seeks innovative ways to create unique and engaging experiences for tourists through advanced technological synergy, like augmented reality (AR) applications. However, current tourist AR solutions face the problem of overwhelming tourists with excessive and poorly personalized information, thus compromising the overall experience. This dissertation aims to address this issue by designing and implementing an AR solution that enables tourists to explore routes in a more effective, immersive, and contextually way. The project seeks to address several key issues, including facilitating easier exploration and navigation, reducing the overload of information, promoting local tourism, and enriching the route experience by making it more educational. By offering personalized information about historical monuments, points of interest, and cultural landmarks, the AR application aims to provide a deeper and meaningful understanding of each location. The primary objective is to establish a mutual relationship between technology and tourism, where AR serves as a powerful tool to create personalized and enriching experiences. By focusing on location-based AR technology, this study develops a system that dynamically adapts to the user's movements, enhancing exploration and navigation. Two historic routes, one in the city of Porto and the other in the city of Chaves, were created to test the solution, selected for their rich cultural and personal significance for the author. This approach not only tested the applicability of the solution across different environments but also allowed for a comprehensive analysis of user experiences in multiple locations and itineraries. Ultimately, this dissertation presents conclusions derived from experimentation and statistical data analysis, confirming the successful achievement of its objectives. It also validates the research hypothesis that the implementation of AR technology in tourist routes significantly enhances the efficiency, immersion, and contextualization in the exploration of these itineraries.